Operative findings after percutaneous pulmonary balloon dilatation of the right ventricular outflow tract in tetralogy of Fallot. Issue 5 (November 1990) - Battistessa, S A; Robles, A; Jackson, M; Miyamoto, S; Arnold, R; McKay, R
Abstract : Since 1983 percutaneous balloon dilatation of the right ventricular outflow tract has been performed as an alternative to surgical palliation in selected cases of tetralogy of Fallot at the Royal Liverpool Children's Hospital. From 31 December 1984 to 31 December 1988, 27 of these patients underwent subsequent surgical correction. Age at operation ranged from 7 to 58 months (median 2.7 years). The mean interval between balloon dilatation and correction was 15.6 months (range 3-39 months). Two patients had a systemic pulmonary shunt operation performed before dilatation and a further five required one afterwards. Overall 20 (74%) patients had some anatomical alteration as the result of balloon dilatation, while in seven (26%) there was no discernible change in the right ventricular outflow tract. There was no consistent relation between the ratio of balloon size to pulmonary annulus diameter and the morphological findings. Balloon dilatation may obviate the need for systemic-pulmonary shunt at the expense of some structural damage, particularly to the posterior cusp. The present data suggest that dilatation does not bring about growth of the annulus to such an extent that transannular patch is no longer needed at intracardiac repair.